A Romantics Chronology, 1780-1832 - Garrett, Martin. author. aut Link
IX, 336 p.
Keywords: This book covers the life and work of a wide range of writers from Coleridge to Wollstonecraft, Hemans, Beckford and their contemporaries. Also encompassing a wealth of material on contexts from the treason trials of 1794 to the coming of gas-light to the London stage in 1817, it provides a panorama of one of the richest periods in British culture.